Effects of Addition of Prosopis Juliflora Fiber on the Physical and Mechanical Properties of Wood Dust and Coir Pith Particle Reinforced Phenol Formaldehyde Hybrid Composite - Athijayamani, A.; Jose, A.Sujin; Ramanathan, K.; Sidhardhan, S. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In this study, Wood Dust (WD)/Phenol Formaldehyde (PF) and Coir Pith (CP)/PF composites were hybridized with the Prosopis Juliflora Fiber (PJF) to obtain the hybrid composites. Composites were prepared by hand moulding technique. The weight percentage of particles and fibers are fixed in the ratio of 1:1. Mechanical properties such as tensile, flexural and impact strengths were evaluated as a function of the particle and fiber loadings. The results show that the properties of both the WD and CP composites obviously improved by the addition of the PJF. The improvement in WD/PF composites was obviously higher than the CP/PF composites for all loadings. The WD/PJF/PF hybrid composites exhibited better tensile (strength of 48.9 MPA and modulus of 1262.1 MPa, respectively), flexural (strength of 55.4 MPa and modulus of 1344.3 MPa, respectively), and impact properties (1.32 KJ/m2).Â 